A Smart Lithium Battery with Shape Memory Function. Issue 4 (2nd December 2021) - Jabbari, Vahid; Yurkiv, Vitaliy; Rasul, Md Golam; Cheng, Meng; Griffin, Philip; Mashayek, Farzad; Shahbazian‐Yassar, Reza
Abstract: Rapidly growing flexible and wearable electronics highly demand the development of flexible energy storage devices. Yet, these devices are susceptible to extreme, repeated mechanical deformations under working circumstances. Herein, the design and fabrication of a smart, flexible Li‐ion battery with shape memory function, which has the ability to restore its shape against severe mechanical deformations, bending, twisting, rolling or elongation, is reported. The shape memory function is induced by the integration of a shape‐adjustable solid polymer electrolyte. This Li‐ion battery delivers a specific discharge capacity of ≈ 140 mAh g ‐1 at 0.2 C charge/discharge rate with ≈ 92% capacity retention after 100 cycles and ≈ 99.85% Coulombic efficiency, at 20 ° C. Besides recovery from mechanical deformations, it is visually demonstrated that the shape of this smart battery can be programmed to adjust itself in response to an internal/external heat stimulus for task‐specific and advanced applications. Considering the vast range of available shape memory polymers with tunable chemistry, physical, and mechanical characteristics, this study offers a promising approach for engineering smart batteries responsive to unfavorable internal or external stimulus, with potential to have a broad impact on other energy storage technologies in different sizes and shapes. Abstract : A smart, flexible lithium battery with shape memory function, which has the ability to restore its shape against severe mechanical deformations upon heating is presented. The shape memory function is induced by integration of a shape‐adjustable solid polymer electrolyte. This smart battery can also be programmed to adjust itself in response to an internal/external heat stimulus for task‐specific and advanced applications.